Properties of Welded Joints in Power Plant - Novotny, Jan; Honzikova, Jarmila; Pilous, Vaclav; Stransky, Karel (Manufacturing Technology Journal, 2015)
This paper deals with evaluation of the controlling processes service reliability of degradation processes leading to embrittlement, fracture at elevated temperatures, fatigue and fatigue fracture with the possible effect of corrosion and with interaction of all the previously mentioned processes.
Keywords: evaluation of the controlling processes; degradation; fracture at elevated temperatures